Analisis Sistem Drainase Di Kawasan Permukiman Pada Ruas Jalan Getah Tunggal Kelurahan Cempaka Kota Banjarbaru - Fathurrahman Fathurrahman; Akhmad Gazali (Media Ilmiah Teknik Sipil, 2019)
Floods that occurred in the city of Banjarbaru especially those that occurred in residential areas caused problems for the community as well as challenges for the government to evaluate the drainage channel in the settlement. The existing rainwater drainage channels need to be reviewed and developed so that they can accommodate the water flowing in the area. One of the settlements that had occurred in the city of Banjarbaru was a residential area in Cempaka Subdistrict, Cempaka Village, precisely on Jalan Getah Tunggal. The data needed in this study are rainfall data, land use data, topographic data and existing data on channel conditions at the study site. Rainfall data were analyzed by Log Pearson III, Gumbel and Iwai Kadoya methods, then tested by Chi Square to choose the distribution of statistics received. The rainfall data was analyzed into the intensity of hourly rain using the mononobe method. Rain intensity is analyzed using a rational method to get a plan debit (Qchannel). Furthermore (the plan) is compared with (Qchannel), and (Qexisting). Based on the calculation results obtained (Qplanning) of 0.76 m3/sec, (Qchannel) of 0.78 m3/sec, (Qexisting) of 0.0645 m3/sec, the comparison results are obtained (Qchannel)>(Qplanning), (Qexisting) <(Qplanning). So that it can be concluded that the causes of flooding and inundation are sediments as high as 70 cm which reduce the storage capacity of the initial dimensions of the channel